Intestinal peroxisome proliferator‐activated receptor α‐fatty acid‐binding protein 1 axis modulates nonalcoholic steatohepatitis. Issue 1 (15th January 2023) - Yan, Tingting; Luo, Yuhong; Yan, Nana; Hamada, Keisuke; Zhao, Nan; Xia, Yangliu; Wang, Ping; Zhao, Changdong; Qi, Dan; Yang, Shoumei; Sun, Lulu; Cai, Jie; et al.
Abstract : Background and Aims: Peroxisome proliferator‐activated receptor α (PPARα) regulates fatty acid transport and catabolism in liver. However, the role of intestinal PPARα in lipid homeostasis is largely unknown. Here, intestinal PPARα was examined for its modulation of obesity and NASH. Approach and Results: Intestinal PPARα was activated and fatty acid‐binding protein 1 (FABP1) up‐regulated in humans with obesity and high‐fat diet (HFD)–fed mice as revealed by using human intestine specimens or HFD/high‐fat, high‐cholesterol, and high‐fructose diet (HFCFD)‐fed C57BL/6N mice and PPARA ‐humanized, peroxisome proliferator response element–luciferase mice. Intestine‐specific Ppara or Fabp1 disruption in mice fed a HFD or HFCFD decreased obesity‐associated metabolic disorders and NASH. Molecular analyses by luciferase reporter assays and chromatin immunoprecipitation assays in combination with fatty acid uptake assays in primary intestinal organoids revealed that intestinal PPARα induced the expression of FABP1 that in turn mediated the effects of intestinal PPARα in modulating fatty acid uptake. The PPARα antagonist GW6471 improved obesity and NASH, dependent on intestinal PPARα or FABP1. Double‐knockout ( Ppara/Fabp1 ΔIE ) mice demonstrated that intestinal Ppara disruption failed to further decrease obesity and NASH in the absence of intestinal FABP1. Translationally, GW6471 reduced human PPARA‐driven intestinal fatty acid uptake and improved obesity‐related metabolic dysfunctions in PPARA ‐humanized, but not Ppara ‐null, mice. Conclusions: Intestinal PPARα signaling promotes NASH progression through regulating dietary fatty acid uptake through modulation of FABP1, which provides a compelling therapeutic target for NASH treatment. Abstract :